2015
DOI: 10.3201/eid2108.142015
|View full text |Cite
|
Sign up to set email alerts
|

Human–Bat Interactions in Rural West Africa

Abstract: Because some bats host viruses with zoonotic potential, we investigated human–bat interactions in rural Ghana during 2011–2012. Nearly half (46.6%) of respondents regularly visited bat caves; 37.4% had been bitten, scratched, or exposed to bat urine; and 45.6% ate bat meat. Human–bat interactions in rural Ghana are frequent and diverse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 12 publications
0
34
0
1
Order By: Relevance
“…Our analysis found that most MERS research articles were published in specialized journals, of which Journal of Virology contained the largest number, followed by Emerging Infectious Diseases and Eurosurveillance. This may be accounted for by their contents, primarily exploring the nature of the viruses of animals, archaea, bacteria, fungi, plants, and protozoa [13][14][15][16][17][18]; by their authorship, as being chosen as target journals by the researchers in the infectious diseases area, and their high frequency of citation.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis found that most MERS research articles were published in specialized journals, of which Journal of Virology contained the largest number, followed by Emerging Infectious Diseases and Eurosurveillance. This may be accounted for by their contents, primarily exploring the nature of the viruses of animals, archaea, bacteria, fungi, plants, and protozoa [13][14][15][16][17][18]; by their authorship, as being chosen as target journals by the researchers in the infectious diseases area, and their high frequency of citation.…”
Section: Discussionmentioning
confidence: 99%
“…Even when some species of viral hemorrhagic fevers have been demonstrated to be hosted in various mammals in the environment, more research is required to identify the natural host of the EVD virus [29] [30]. This will enable scientists develop appropriate strategies to protect the populations against infections.…”
Section: Discussionmentioning
confidence: 99%
“…Vora et al report a study done after a bat festival in Idandre, Nigeria, where males entered caves to hunt bats. Many of the participants sustained scratches and bites from bats, but none reported a serious illness [70]. In 2008, two patients developed Marburg hemorrhagic fever after exploring Python cave in Uganda, the fatal case was imported to the Netherlands and another was imported to Colorado, USA.…”
Section: Spelunkingmentioning
confidence: 99%